2022
DOI: 10.1002/pro.4295
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Angiomotin‐like 1 and Yes‐associated protein form a dynamic complex

Abstract: Multivalent complexes formed between the cancer-promoting transcriptional co-activator, Yes-associated protein (YAP), and proteins containing short linear motifs of type PPxY modulate cell proliferation and are attractive therapeutic targets. However, challenges producing PPxY polypeptides containing the full binding domain has limited understanding of the assembly process. Here, we successfully produced a polypeptide containing the complete set of three PPxY binding sites of Angiomotin-like 1 (AMOTL1), a scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We have reserved nine IDPs for testing SeqDYN (parameterized on the training set of 45 IDPs). The level of disorder in these test proteins also spans the full range, from absence of secondary structures [ChiZ N-terminal region (12), Pdx1 C-terminal region (11), and TIA-1 prion-like domain (17)] to presence of transient short helices [synaptobrevin-2 (7), α-endosulfine (38), YAP (6), angiomotin-like 1 (AMOTL1) (39)] to formation of stable long helices [FtsQ (13) and CAHS-8 (9)]. For eight of the nine test IDPs, the RMSEs of SeqDYN predictions are lower than the experimental values, by an average of 0.62 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reserved nine IDPs for testing SeqDYN (parameterized on the training set of 45 IDPs). The level of disorder in these test proteins also spans the full range, from absence of secondary structures [ChiZ N-terminal region (12), Pdx1 C-terminal region (11), and TIA-1 prion-like domain (17)] to presence of transient short helices [synaptobrevin-2 (7), α-endosulfine (38), YAP (6), angiomotin-like 1 (AMOTL1) (39)] to formation of stable long helices [FtsQ (13) and CAHS-8 (9)]. For eight of the nine test IDPs, the RMSEs of SeqDYN predictions are lower than the experimental values, by an average of 0.62 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, whereas the two peaks have approximately equal heights in the measured R 2 profile, the predicted peak height around Phe200 is too low. SCSs indicate helix propensity around both R 2 peaks (39). PsiPred also predicts helix in both regions, but only five and two residues, respectively, survive after filtering, which are too short for applying a helix boost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when it binds to its partners or undergoes modifications at the binding interface, YAP acquires a more defined structure, facilitating specific interactions. 42 Arginine methylation disperses the charge over more atoms, and subsequently alters its hydrophobic properties, leading to a change in the binding of methylarginine to specific proteins and regulating their functions. 43 Supporting this notion, we found that the asymmetric dimethylation at R124 of YAP (YAP-R124me2a), catalyzed by PRMT1, enhanced the YAP-SOX9 interaction.…”
Section: Discussionmentioning
confidence: 99%